GROSS ANATOMICAL AND MOROPHMETRICAL STUDIES TO THE SKULL BONES OF THE LOCAL RABBIT (ORYCTOHGUSCUNICULUS ). - Salih K.M (Basrah Journal of Veterinary Research)
Ten adult rabbit (5male and 5 female ) were used for gross anatomical and biometrical studies .The main characteristics feature of the local rabbit skulls are : in dorsal surface there are a shallow external sagittle crest , the frontal bone has anterior and posterior supraorbital process , the external acoustic meatus is a short wide bony tube directed caudodorsally , the orbita are large , the external surface of the maxilla is pitted by numerous small opening (fenestrated). A total of 16 linear measurement estimated in the rabbit skulls .There are significant difference between males and females observed in bizygomatic distance , basion-bragma height , maxilla- alveolar length , orbital height and foramen magnum breadth